Respuesta :
First distribute the 3
12y - 15 = 69
Subtract -15 from both sides
12y = 84
y=7
PROOF:
3 (4 *7 - 5)
3 (28-5)
3 (23) = 69
12y - 15 = 69
Subtract -15 from both sides
12y = 84
y=7
PROOF:
3 (4 *7 - 5)
3 (28-5)
3 (23) = 69
Y= 7 because if you divide both sides by three you get 3(4y -5) ÷ 3 and 69 ÷ 3 and you simplify it you get 4y - 5 = 23 then add 5 to both sides 4y - 5 + 5 = 23 + 5 simplify that you get 4y = 28 divide again but divide both sides by 4
4y ÷ 4 28 ÷ 4 simplify one more time and y = 7!
4y ÷ 4 28 ÷ 4 simplify one more time and y = 7!